2017
DOI: 10.3892/mmr.2017.7610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-osteoporotic effects of tetramethylpyrazine via promoting osteogenic differentiation and inhibiting osteoclast formation

Abstract: Long‑term glucocorticoid therapy results in various side effects, including a high incidence of glucocorticoid‑induced osteoporosis (GIOP), which is the most common form of secondary osteoporosis. Excess glucocorticoids reduce the viability of bone marrow‑derived mesenchymal stem cells (BMSCs) and prolong osteoclast survival. These two types of cell are essential in the balance between bone formation and resorption. Tetramethylpyrazine (TMP), the pharmacologically active component extracted from Chuanxiong, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Simultaneously, Lig can inhibit the expression of the endothelial cell adhesion molecule of E-selectin, P-selectin and intercellular adhesion molecule-1 (Yang et al, 2008 ). Ultimately, they can alleviate inflammatory of myocardial I/R injury through inhibiting the expression of tumor necrosis factor-α (Hu et al, 2008 ), IL- 6 (Hu et al, 2008 ; Shang et al, 2008 ; Wang et al, 2017 ), and/or promoting the expression of HSP (Chen et al, 2007 ; Shang et al, 2008 ); (3) inhibition of apoptosis (Duan et al, 2000 ; Chen et al, 2007 ; Zhang et al, 2007 ) through increasing the expression of Bcl-2 (Liu and Niu, 2011 ; Zhai et al, 2011 ; Zhao et al, 2012 ), reducing the expression of Bax protein (Liu and Niu, 2011 ; Zhai et al, 2011 ; Zhao et al, 2012 ) in the myocardium, and down-regulating the expression of caspase and Fas (Zhang et al, 2007 ); (4) metabolism mechanism through increasing the expression of the protein of p-Akt (Lv et al, 2012 , 2016 ) and content of ATP in myocardium (Lv et al, 2016 ) with activating PI3K/Akt signal pathway (Lv et al, 2012 , 2016 ); (5) improvement of the circulation by enhancing the expression of NO (Wan et al, 1998 ; Yang and Rui, 2007 ; Gu et al, 2009 ; Li and Li, 2010 ) via up-regulating the expression of NOS (Li et al, 2006 ; Xu and Zhang, 2006 ; Yang and Rui, 2007 ; Gu et al, 2009 ). A schematic representation of cardioprotective mechanism of Lig for myocardial I/R injury was summarized in Figure 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, Lig can inhibit the expression of the endothelial cell adhesion molecule of E-selectin, P-selectin and intercellular adhesion molecule-1 (Yang et al, 2008 ). Ultimately, they can alleviate inflammatory of myocardial I/R injury through inhibiting the expression of tumor necrosis factor-α (Hu et al, 2008 ), IL- 6 (Hu et al, 2008 ; Shang et al, 2008 ; Wang et al, 2017 ), and/or promoting the expression of HSP (Chen et al, 2007 ; Shang et al, 2008 ); (3) inhibition of apoptosis (Duan et al, 2000 ; Chen et al, 2007 ; Zhang et al, 2007 ) through increasing the expression of Bcl-2 (Liu and Niu, 2011 ; Zhai et al, 2011 ; Zhao et al, 2012 ), reducing the expression of Bax protein (Liu and Niu, 2011 ; Zhai et al, 2011 ; Zhao et al, 2012 ) in the myocardium, and down-regulating the expression of caspase and Fas (Zhang et al, 2007 ); (4) metabolism mechanism through increasing the expression of the protein of p-Akt (Lv et al, 2012 , 2016 ) and content of ATP in myocardium (Lv et al, 2016 ) with activating PI3K/Akt signal pathway (Lv et al, 2012 , 2016 ); (5) improvement of the circulation by enhancing the expression of NO (Wan et al, 1998 ; Yang and Rui, 2007 ; Gu et al, 2009 ; Li and Li, 2010 ) via up-regulating the expression of NOS (Li et al, 2006 ; Xu and Zhang, 2006 ; Yang and Rui, 2007 ; Gu et al, 2009 ). A schematic representation of cardioprotective mechanism of Lig for myocardial I/R injury was summarized in Figure 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The activity and number of osteoclasts after hydrogel injection were further examined by TRAP staining. TRAP, a metabolic enzyme specifically expressed by mature osteoclasts, is closely associated with osteolysis in osteoblasts . TRAP is expressed in osteoclasts, and the dark-stained cells with burgundy cytoplasm are osteoclasts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…TRAP, a metabolic enzyme specifically expressed by mature osteoclasts, is closely associated with osteolysis in osteoblasts. 38 TRAP is expressed in osteoclasts, and the dark-stained cells with burgundy cytoplasm are osteoclasts. Osteoclasts are effector cells of bone resorption.…”
Section: Nap Alen/hap Inhibits the Biological Function Of Bmdmsmentioning
confidence: 99%
“…Further studies suggested that TMP down-regulated RANKL and IL-6, promoted osteogenesis and inhibited osteoclastogenesis to ameliorate the change in bone mass in the GIOP state. 54 In addition, LIG protected chondrocytes against SNP-induced apoptosis and delayed articular cartilage degeneration via suppression of the JNK and p38 MAPK pathways. 55 Recently, Dong et al 56 discovered that the CX ethanol extract (CXE) could be used to treat OP by attenuating cellular reactive oxygen species levels and inhibiting osteoblast apoptosis through PI3K/Akt signaling pathway.…”
Section: Pharmacological Effects Of CXmentioning
confidence: 99%